The Human Soul as a Symbolic Message in Contemporary Arts in Malaysia: A Study of Daud Rahim’s Works - Issarezal Ismail; Ishak Ramli; Mohd Daud Abdul Rahim; Erry Arham Azmi (Institut Seni Indonesia Yogyakarta, 2023)
The objectives of this study are to describe the structure of the message and to interpret the meaning of the use of symbols which are the core of a message in the context of the soul through Daud Rahim’s series of paintings entitled “Jiwa” (2013). This study was carried out to approach, understand, and at the same time explain the human soul as a symbolic message in contemporary art in Malaysia concerning aspects of the structure, content, and function of messages from a number of works produced by Daud Rahim. An art study methodology that focuses on an in-depth and comprehensive explanatory system has been used based on an analysis model that has been developed from a relevant conceptual framework which is Human Spirit as a Symbolic Message in Fine Art. The results of the analysis show that the signs and symbols of Daud Rahim’s works want to express the symbolic message of a human phenomenon involving modern humans who are unable to control their passions, so they become egocentric figures who are obsessed and greedy with the material world so that it is difficult to activate feelings of love and affection. affection and slowly erodes the social relations around him. In conclusion, visual artwork is a nonverbal communication tool or media created by artists to convey messages to others regarding issues or problems of humanity, society, and culture, which are repackaged through the use of certain signs and symbols. Jiwa Manusia sebagai Pesan Simbolik dalam Seni Rupa Kontemporer di Malaysia: Kajian terhadap Karya-karya Daud Rahim. Penelitian ini bertujuan untuk mendeskripsikan struktur pesan dan memaknai penggunaan simbol-simbol yang menjadi inti pesan dalam konteks jiwa melalui lukisan seri Daud Rahim berjudul “Jiwa” (2013). Penelitian ini dilaksanakan untuk mendekati, memahami, dan sekaligus menjelaskan jiwa manusia sebagai pesan simbolik dalam seni rupa kontemporer di Malaysia menyangkut aspek-aspek struktur, isi, dan fungsi pesan dari sejumlah karya yang dihasilkan oleh Daud Rahim. Metodologi kajian seni memfokuskan pada sistem penjelasan yang bersifat mendalam dan menyeluruh telah digunakan berdasarkan pada model analisis yang telah dibangun dari konsep-konsep yang relevan yaitu kerangka konseptual spiritual manusia sebagai pesan simbolik dalam seni rupa. Hasil analisis menunjukkan bahwa tanda dan simbol dari karya-karya Daud Rahim mengungkapkan pesan simbolik dari sebuah fenomena kemanusiaan yang melibatkan manusia modern yang tidak mampu mengawal hawa nafsu sehingga menjadi sosok-sosok egosentris yang obsesif dan rakus dengan dunia material sehingga sulit mengaktifkan perasaan kasih dan sayang sehingga secara perlahan-lahan mengikis hubungan sosial di sekelilingnya. Kesimpulannya, karya seni visual ialah alat atau media komunikasi non-lisan yang diciptakan oleh seniman untuk menyampaikan pesan kepada orang lain mengenai isu atau masalah kemanusiaan, masyarakat, dan budaya yang dibentuk semula melalui penggunaan tanda dan simbol tertentu.